Booster dose with the BNT162b2 vaccine in the population that received the complete immunization schedule for COVID-19 in Peru: A critical analysis of the current evidence - Toro-Huamanchumo, Carlos J. (2021)
Background: In Peru, the current immunization schedule for COVID-19 includes BBIBP-CorV, BNT162B2 and ChAdOx1 nCoV-19 vaccines. Although the full immunization schedule is two doses, some countries have recently included a booster dose to their schedule. Methods: We conducted a search for scientific evidence on the efficacy and safety of booster vaccination with BNT162b2 vaccine in a population with a complete vaccination schedule for COVID-19 in Peru. Evidence: Four evidence-based recommendation documents, one observational study and three ongoing phase III clinical trials were included for analysis. Conclusion: To date, there is insufficient evidence on the efficacy of adding a booster dose to the immunization schedule for COVID-19. The available evidence does not justify the use of a booster dose of BNT162B2 vaccine in a population that has previously received two doses of the aforementioned vaccines.